Influência da diminuição da cobertura da floresta nativa na comunidade de Odonata (Insecta) na Amazônia Oriental. - FERREIRA, Driane Cardoso (2022)
The ongoing conversion of native forest to anthropic purposes (eg. cattle raising) is increasingly affecting the physical habitat of Amazonian aquatic streams. The objective of the study was to asses the influence of the loss of natural vegetation cover on the community structure of Odonata (Anisoptera and Zygoptera), testing the hypothesis that there would be loss of Zygoptera diversity and an increase in diversity of Anisoptera in areas with lower percentage of native forest cover, due to the different environmental requirements of the suborders. For this, we collected in 50 streams located in the municipality of Paragominas-Pará. TITAN identified nine species associated with native forest cover, six species associated with more forested environments and three species associated to environments with lower vegetation cover. Our results suggest that preserving the natural vegetation cover with riparian vegetation is fundamental for the maintenance of the physical characteristics of the streams and for the structure of the Odonata assemblies. The adults of Odonata are associated with the quality of the aquatic and terrestrial environment since they responded in diversity in 500m of distance around the streams.